PENGARUH KEPUASAN KERJA, PROFESIONALISME, DAN PENERAPAN TEKNOLOGI INFORMASI TERHADAP KINERJA AUDITOR (Studi pada Kantor BPK RI Perwakilan Provinsi Aceh) - Ibnu Gautama S; Muhammad Arfan (Program Magister Akuntansi Unsyiah, 2010)
This study is done at BPK RI branch office in Aceh Province which aim to know the influence of job satisfaction, professionalism, and information technology application toward auditor performance either simultaneously or partially.This research uses sample method. Respondents of this research are auditors at BPK RI branch office in Aceh Province. This research uses 52 auditors as samples of population 94 auditors by using stratified random sampling. The data used are primary data by using questionnaires to the respondents directly. Ddata are analyzed by using multiple linear regression.Results of this research indicate that by simultaneously job satisfaction, professionalism, and information technology application influence significanly toward auditor performance. Partially. job satisfaction, professionalism, and information technology application also influence significanly toward auditor performance. Keyword: job satisfaction, professionalism, information technology application and auditor performance.